Learning in Collective Impact Processes: Complexity and Change - Margaret L. Cain; Stephanie Rokich (Adult Education Research Conference, 2014)
This study explored the learning among participants in collective impact community efforts to address social issues. Research focused on the process of learning as co-emergence and the ways in which learning affected participants’ understandings of root causes of and systems involved in the social issues.